DYSMORPHIC features and adult short stature: possible clinical markers of KBG syndrome - Mattei, Davide (Ital J Pediatr, 2021)
BACKGROUND: Growth monitoring is an essential part of primary health care in children and short stature is frequently regarded as a relatively early sign of poor health. The association of short stature and dysmorphic features should always lead to exclude an underlying syndromic disorder. CASE PRESENTATION: We report the case of an Indian school-aged boy with dysmorphic features, intellectual disability and a clinical history characterized by seizures and hearing problems. Although his height was always included in the normal range for age and sex throughout childhood, he presented a short near-adult stature in relation to his mid-parent sex-adjusted target height. This is probably due to a rapidly progressive pubertal development. CONCLUSIONS: In the presence of characteristic dysmorphic features, intellectual disability, seizures and hearing problems, KBG syndrome should always be considered. This emergent condition presents a wide spectrum of clinical phenotypes and is often associated with adult short stature.